Pengaruh E-Commerce Terhadap Pendapatan UMKM Yang Bermitra Gojek Dalam Masa Pandemi Covid-19 - Rianty, Martha; Rahayu, Pipit Fitri (Akuntansi dan Manajemen, 2021)
Tight business competition, especially during the COVID-19 pandemic until the second semester in 2021, is still very much felt. Consumer incomes are starting to decline and the urgency of using technology is due to direct buying activities that are recommended to use electronic money more nowadays. The emergence of the e-commerce market has created vast market opportunities for retailers and logistics service providers, can increase purchase and sales satisfaction and can facilitate the ability of logistics service providers to manage greater. This is what makes us as researchers want to know how much influence e-commerce has on income, especially for MSMEs that have used e-commerce in the South Sumatra area. The population in this study is MSME users of e-commerce. The sampling technique used non-probability sampling with purposive sampling type obtained as many as 397 samples. By using the multiple linear regression technique, the results obtained that the interface, navigation, content, and reliability variables have a significant effect on the income of MSMEs in South Sumatra during the COVID-19 pandemic, while technical variables have no effect on the income of MSMEs in South Sumatra.